Optimization of Flash Extraction of Akebia trifoliata Seed Oil by the Box-Behnken Response Surface Methodology and Comparison of Oil Yields from Different Origins - Rong-Rong Huang (Journal of Chemistry, 2022)
The aim was to optimize the extraction process of Akebia trifoliata seed oil. Using Akebia trifoliata seed as raw material, the oil extraction rate was used as index. The effect of flash extraction on the yield of Akebia trifoliata seed oil was investigated. Taking the liquid-material ratio, extraction voltage, and extraction time as the investigation factors and the oil extraction rate of Akebia trifoliata seed as the response value and on the basis of the single-factor test, the extraction process of Akebia trifoliata seed oil was optimized by the Box-Behnken response surface method. The oil yields of Akebia trifoliata seeds from different origins in China were compared. The experimental results showed that the optimum technological conditions for flash extraction of Akebia trifoliata seed oil were as follows: liquid-material ratio, 12 : 1; extraction voltage, 150 V; extraction time, 90 s; and oil yield of Akebia trifoliata seed, 19.83%. For comparison, it is found that the oil yield of Akebia trifoliata seed produced in Qujing of Yunnan is relatively the highest, followed by Tongren of Guizhou and Zhangjiajie of Hunan; the oil yield of Akebia trifoliata seed produced in Shimian of Sichuan is the lowest. The flash extraction process of Akebia trifoliata seed oil is reasonable, and the oil yield of Akebia trifoliata seed produced in Qujing of Yunnan, China, is relatively the highest. It provides a theoretical and experimental reference for the research and development of Akebia trifoliata seed oil.